Transmission of Helminths between Species of Ruminants in Austria Appears More Likely to Occur than Generally Assumed - Winter, Jakob; Rehbein, Steffen; Joachim, Anja (Frontiers in Veterinary Science, 2018)
Helminth infections of the gastrointestinal tract and lungs can lead to devastating economical losses to the pastoral based animal production. Farm animals can suffer from malnutrition, tissue damage and blood loss resulting in impaired production traits and reproduction parameters. In Austria, pastures grazed by sheep, goats and cattle overlap with the habitats of several species of wild cervids (roe deer, red deer, sika deer, fallow deer) and bovids (mouflon, chamois, ibex), and transmission of parasites between different ruminant species seems likely. A complete and updated overview on the occurrence of helminths of domestic and wild ruminants in Austria is presented. Based on these data, intersections of the host spectrum of the determined parasites were depicted. The “Liability-index” was applied to identify the ruminant species which most likely transmit parasites between each other. A degree for host-specificity was calculated for each parasite species based on the average taxonomic distance of their host species. Of the 73 identified helminth species 42 were identified as generalists, and 14 transmission experiments supported the assumed broad host specificity for 14 generalists and one specialist helminth species. Overall 61 helminths were found to infect more than one host species, and four were found in all ten ruminant species investigated. From these analyses it can be concluded that a number of helminth parasites of the gastrointestinal tract and the lungs are potentially transmitted between domestic and wild ruminants in Austria. For some parasites and host species, experimental evidence is in support for possible transmission, while for other such studies are lacking. Host preference of different genotypes of the same parasite species may have a confounding effect on the evaluation of cross-transmission, but so far this has not been evaluated systematically in helminths in Austria. Further studies focusing on experimental cross-transmission and genetic characterization are needed to define the potential consequences for the epidemiology of those parasites, animal welfare and economic impact.